Diagnóstico De Aprobación De La Certificación Internacional ESOL Examinations En La Modalidad Extensión Del Centro De Idiomas - ESPOCH - Enrique Jesús Guambo Yerovi; Marcelo Eduardo Allauca Peñafiel (European Scientific Journal, ESJ, 2018)
This paper focuses on diagnosing and determining the number of students who obtained the International Certification of ESOL Examinations of Cambridge University, which was formed in the Extension Modality of the Language Center. For this reason, this study was carried out based on the academic follow up of those students who passed or failed the 8 levels of English. This was done with a total of 680 hours, planned through the dimensions of a new curriculum, designed within the project titled “Strengthening of the Extension Modality in the Language Center at the Higher Polytechnic School of Chimborazo” based on an academic text of Cambridge University. The results correspond to a total of 122 students of 4 promotions that were evaluated by skills and according to parameters established by the staff of the University of Cambridge ESOL Examinations. This, however, enabled us to ascertain the number of certifications recognized by the Common European Framework, obtained by the students in levels A2, B1, and B2.